Phytochemicals, α-glucosidase and α-amylase Inhibitory Efficiency of Brittle Wort (Chara corallina) Extract - Chankaew, Wanninee; Phetkul, Uraiwan; Srimoon, Rawinipa (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
This research is the first to evaluate brittle wort (Chara corallina) extract for phytochemical content and inhibitory effects against a-glucosidase and a-amylase activities. An ethanolic extract of C. corallina had the strongest enzyme inhibitory effect. The inhibition efficiencies of all extracts against a-amylase were more potent than those against a-glucosidase, with IC50 values of 8.43±0.18 mg/mL against a-glucosidase and 1.78±0.07 against a-amylase. Inhibition efficiency was related to total phenolic content, DPPH radical scavenging activity, ATBS radical scavenging activity and metal-chelation activity of the extracts. Phytochemical screening of the ethanolic extract demonstrated the presence of the triterpenoid β-sitosterol. These findings provide useful supporting data for further applications of C. corallina extract.